Una tumba en Isfahan: Claudius James Rich (1786-1821) y los orígenes de la arqueología en Oriente - Córdoba Zoilo, J. M. (ISIMU, 2016)
In the course of a visit to Isphahan, the fortuitous meeting with the grave of Cl.J. Rich suggests the evocation of the Resident’s role in the history of mesopotamian archaeology. Works and field’s activity show a natural intuition and the early practice of a veritable pioneer. His role show very clear in the way of P.E. Botta and A.H. Layard.